Handbook of communication in organisations and professions - Candlin, Christopher; Sarangi, Srikant, 1956- (Handbooks of applied linguistics, 2011)
This volume presents mayor contributions of Applied Linguistics to the understanding of communications in the professions. The first two parts of this book deal with the theoretical and methodological orientations of professional communication studies, the history and development of professional communication studies, highlighting the discursive turn of Applied Linguistic research that goes far beyond the established paradigm of Language for Specific Purposes. The third part - the core of this book - presents research into professional practices from various domains (e.g. law, healthcare, business and management, organizations), sites of engagement (as e.g. lawyer-client-conference, doctor-patient interaction) and with respect to different themes that are generalizable across domains and sites (as e.g. communicative aspects of action and practice, of assessment and appraisal). In the final part, professionals from various domains evaluate the contribution to their work so far made by Applied Linguistics.